Recuperação de área degradada pela atividade minerária: análise da efetividade legal em Minas Gerais - Lemos, Elianne Christine (2015)
The study’s goal was analyze the accomplishment of environmental legislation as regards the recovery of degraded areas by mining activity. According to Republic Constitution, the sponsor of mineral resources’ exploration needs to restore the degraded environment. Maintenance of an ecologically balanced environment is essential to support life in all its forms. On the other hand, mining industry is essential for country’s economic development. Thus, it’s necessary to confront two essentials elements, first, economical and industrial evolution provided by mining activity constitutionally guaranteed and, second, the right of a balanced environment, law also preserved under the constitution aspect. Such assumptions often accommodate conflicting interests, involving the State as mineral patrimony manager, the miner sponsor who naturally concern in earning profits, the person who owns surface’s rights that support the burden of mining activity in his property and, mainly, environmental interests, whose focus will be prioritized. With unique and convergent features, this branch of law science determines that entrepreneurs have to follow the protection environment assumptions. The research’s aim was to detect the effectiveness of enforcement of recovery’s legislation, based on the nuances of the Degraded Areas Recovery Plan (DARP), appointed by the legislator as a solution to the impasse caused by mining activity. The problem consists of establishing it in the juridical system, a considerable progress was obtained in environmental legislation, however, little is known about the effectiveness based on application. The methodology focused on analysis of legal documents filed in environmental public departments, as well as, through interviews with professionals from the environmental and mining sectors. Therefore, the compliance with environmental legislation reconciled to factual execution of DARP’s, demonstrated that there is a route to be conquered, to achieve full effectiveness of the legislation to recover degraded areas by mining activity. In spite of the legislation, in the federal and state of Minas Gerais scope, were considered efficient for conducting the entrepreneur to restore the degraded area, the law enforcement of Degraded Areas Recovery Plan was inefficient, compromising legislation in its legislative scope.